Batasan Melawan Hukum dalam Perdata dan Pidana Pada Kasus Persekongkolan Tender - Siti Anisah; Trisno Raharjo (Fakultas Hukum Universitas Islam Indonesia, 2018)
Resolution of alleged tender conspiracy based on Law no. 5 of 1999 and Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 has resulted in different decisions. This can be seen in the case of the conspiracies of the tender of the sales of two VLCC tankers Hull 1540 and 1541, Indomobil tender on May 30, 2002, procurement of legislative election ink in 2004, and electronic ID card in 2011 until 2012. This normative research analyzed the intercept between violating the existing laws in terms of criminal law and civil law, and the violation of laws both civil and criminal law in the case of tender conspiracy. The study concluded that, first, the shift in understanding about the unlawful nature (wederrechtelijk) occurs in criminal law, not only based on the criminal law (onwetmatige) but also involves the criteria of violating civil law (onrechmatige), which includes the violation of propriety in community. This is used in criminal law to interpret law violation in a material sense. Nevertheless, there are still different opinions among criminal law experts whether the nature of material law violation only has negative function or has positive function as well. Second, the violation of law that is generally defined in civil law and known in criminal law as a crime in material sense, can be limited by interpretation to determine forbidden acts known as schutznormtheorie or doctrine of relativity. Along with the understanding of law enforcement personnel and jurisprudence, it can be said that the barriers of law violation in criminal law and civil law have gone when the tender conspiracy case already violates the sense of justice in society.